Antidepressant activity of the pyrrolo[1,2a][1,4]diazepine GMAL-24 in a forced swimming test in mice - A. O. Korolev; A. V. Volkova; Ya. S. Kozin; G. V. Mokrov; T. A. Voronina; T. S. Kalinina (LLC "Publisher OKI", 2023)
The antidepressant activity of pyrrolo[1,2a][1,4]diazepines (GMAL-24, GMAL-27, GMAL-31, GMAL-32 and GMAL-33) synthesized at the V.V. Zakusov Research Institute of Pharmacology in a forced swimming test on male outbred mice was studied. The compounds were tested in the dose range from 1.5 mg/kg to 20 mg/kg, the reference group received tricyclic antidepressant amitriptyline at a dose of 10 mg/kg, and the control group received 0.5 ml of saline solution. All injections were performed intraperitoneally. After GMAL-27 administration immobilization time was decreased of 1.78, 1.64 and 1.74 times, respectively, compared with the control in all three studied doses (1.5 mg/kg, 5 mg/kg and 10 mg/kg), without signiﬁcant diﬀerences from the control (p = 0.1340; p = 0.2748; p = 0.2214, respectively). The compound GMAL-31 in doses from 1.5 mg/kg to 20 mg/kg had no eﬀect on the duration of immobilization compared to the control group of mice. It was established that the compound GMAL-24 at doses of 5 mg/kg and 10 mg/kg signiﬁcantly reduced the periods of immobilization compared to the control group and did not diﬀer in this parameter from the comparison drug, which indicates an antidepressant eﬀect comparable to the eﬀect of amitriptyline.